Pilihan Bahasa Masyarakat di Kota Makassar pada Acara Makassar Culinery Night (MCN) - Nur Aminah Reski; Mayong Mayong; Idawati Idawati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to examine the language choices used by the Makassar community in interactions at the Makassar Culinary Night (MCN) event, as well as the factors that influence it using the SPEAKING model from Dell Hymes as an analytical framework. Data were collected through participant observation, in-depth interviews, and questionnaires involving traders, visitors, and event organizers. The results of the study indicate that Indonesian dominates in buying and selling transactions, while code switching and code mixing with Makassar and Bugis languages ​​are often used as strategies to express identity and solidarity. In addition, factors such as the situation (setting), participants, communication goals (ends), sequence of speech (act sequence), tone (key), means (instrumentalities), social norms, and conversational genres collectively shape the pattern of language choices. These findings emphasize that language choices not only function as a means of communication, but also as a means to assert social status, build interpersonal relationships, and express cultural pride. Linguistic dynamics in multicultural public spaces, such as MCN, reflect the flexibility and creativity of urban community discourse. This study is expected to be a basis for the development of inclusive language policies that are responsive to the communication needs of the Makassar community.